DEVICE APPLICATIONS OF TIME ON PC USING MICROSOFT VISUAL BASIC 6.0 - Fritz Manugi Maradona Napitupulu; Yulina, SKom, MMSI Yulina, SKom, MMSI (Jurnal Sistem Informasi, 2007)
With the progress of the development of increasingly sophisticated informationtechnology, computers play an important role in it. Moreover, computers areequipped with facilities and infrastructure are developed at this time because it makesusers forget to use the computer in a long time without optimizing the time to doanother job.Alarm is a media alert while taking a break can be useful in improving. Therefore thealarm on the PC is expected to help computer users in role in reminding the thingsnecessary to be done in optimizing the time.